2006
DOI: 10.3354/ame044253
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an estuarine plume and marine sewage outfall on the dynamics of coastal bacterioplankton communities

Abstract: Marine bacterioplankton in the coastal region off Aveiro (NW Portugal) develop under the influence of the plume of a mesotrophic estuarine system (Ria de Aveiro) and, more recently, under the influence of the discharges of a marine sewage outfall (S. Jacinto). In an attempt to compare the degree of disturbance introduced by these 2 features to the abundance of sewage bacteria and heterotrophic activity of natural bacterioplankton, water samples were collected at 10 offshore and nearshore locations. Rates of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Bacterioplankton communities in riverine and estuarine environments are responsible for water purification processes and are influenced by watershed usage [3][4][5][6][7][8]. Shifts in microbial communities along the salinity gradient formed by the mixing of freshwater and seawater are commonly observed in estuaries [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterioplankton communities in riverine and estuarine environments are responsible for water purification processes and are influenced by watershed usage [3][4][5][6][7][8]. Shifts in microbial communities along the salinity gradient formed by the mixing of freshwater and seawater are commonly observed in estuaries [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At atoll scale, bacterioplankton abundances and productions were significantly correlated with TTC concentrations in May, and with SF in October, respectively (Table 4; Figure 3). This may result from the direct discharge of heterotrophic bacteria and the stimulation of the autochthonous marine community by the release of sewage-derived organic substrates, as demonstrated by Cunha and Almeida (2006) in the coastal region off Aveiro (NW Portugal). The data presented here showed that the dilution and the mortality processes were not sufficient to avoid the presence of FIB in these stations.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, when, where, and how OM is decomposed into nutrients and CO 2 is not fully understood in tropical mangrove ecosystems (Cai 2011). Extracellular enzymatic activities constitute the limiting step of the whole process of OM cycling (Arnosti 2011) and thus, the turnover rates of various compounds have been used to evaluate the efficiency of the microbial community to mineralise OM in coastal waters (Patel et al 2000, Cunha and Almeida 2006, Bhaskar and Bhosle 2008, Lamy et al 2009). The leucine-aminopeptidase activity (exoproteolytic activity, EPA) is one of the most commonly used indicators of OM hydrolysis.…”
Section: Introductionmentioning
confidence: 99%